2018
DOI: 10.3748/wjg.v24.i2.266
|View full text |Cite
|
Sign up to set email alerts
|

Predictive and prognostic value of serum AFP level and its dynamic changes in advanced gastric cancer patients with elevated serum AFP

Abstract: AIMTo investigate predictive and prognostic value of serum alpha-fetoprotein (AFP) level and its dynamic changes in patients with advanced gastric cancer with elevated serum AFP (AFPAGC).METHODSOne hundred and five patients with AFPAGC were enrolled in the study, and all of them underwent at least one cycle of systemic chemotherapy at our institute and had serum AFP ≥ 20 ng/mL at diagnosis or recurrence. Clinicopathologic features, serum AFP level at diagnosis and changes during treatment, first-line chemother… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 28 publications
2
26
0
Order By: Relevance
“…[ 27 ] In the present study, LM was present in 39.6% of the 96 patients with AFPGC. According to the NCCN Clinical Practice Guidelines in Oncology: GC, [ 20 ] LM of GC should be directly classified as stage IV, which is associated with poor prognosis, [ 28 ] as confirmed in the present study. It is recommended that for patients with operable GC, radical gastrectomy is the preferred treatment.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…[ 27 ] In the present study, LM was present in 39.6% of the 96 patients with AFPGC. According to the NCCN Clinical Practice Guidelines in Oncology: GC, [ 20 ] LM of GC should be directly classified as stage IV, which is associated with poor prognosis, [ 28 ] as confirmed in the present study. It is recommended that for patients with operable GC, radical gastrectomy is the preferred treatment.…”
Section: Discussionsupporting
confidence: 69%
“…[ 22 – 24 ] Recently, Wang et al suggest that triplet chemotherapy regimens may be a better choice for GC patients with markedly elevated AFP. [ 20 ] The present study compared 4 general chemotherapy regimens, including monotherapy, docetaxel-cis-platinum-fluorouracil acid, FOLFOX, and oxaliplatin-xeloda (capecitabine), with palliative therapy, in terms of OS and PFS, and demonstrated that compared with palliative treatment, there was no significant difference in the OS and PFS between the 4 chemotherapy regimens ( P > 0.05).…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Intensive treatment (triplet regimen) seems to have slightly better disease control rate with 13.9 months of median OS. 25 …”
Section: Discussionmentioning
confidence: 99%